2008
DOI: 10.1073/pnas.0800163105
|View full text |Cite
|
Sign up to set email alerts
|

Critical regulation of TGFβ signaling by Hsp90

Abstract: Transforming growth factor ␤ (TGF␤) controls a diverse set of cellular processes by activating TGF␤ type I (T␤RI) and type II (T␤RII) serine-threonine receptor kinases. Canonical TGF␤ signaling is mediated by Smad2 and Smad3, which are phosphorylated in their SXS motif by activated T␤RI. The 90-kDa heat-shock protein (Hsp90) is a molecular chaperone facilitating the folding and stabilization of many protein kinases and intracellular signaling molecules. Here, we present evidence identifying a critical role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
105
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(116 citation statements)
references
References 36 publications
10
105
0
1
Order By: Relevance
“…12,14 Interestingly, a recent study has identified TbRI and TbRII as Hsp90 client proteins. 15 However, the clinical significance of Hsp90 inhibitors in disease models with aberrant TGF-b responses remains to be determined. Here, we examined whether Hsp90 might regulate TGF-b1 signaling in renal cells and determined the effect of Hsp90 inhibitors in cultured renal cells and in a model of renal fibrosis.…”
mentioning
confidence: 99%
“…12,14 Interestingly, a recent study has identified TbRI and TbRII as Hsp90 client proteins. 15 However, the clinical significance of Hsp90 inhibitors in disease models with aberrant TGF-b responses remains to be determined. Here, we examined whether Hsp90 might regulate TGF-b1 signaling in renal cells and determined the effect of Hsp90 inhibitors in cultured renal cells and in a model of renal fibrosis.…”
mentioning
confidence: 99%
“…In this complex, the N-terminal part of Smad7 facilitates Smurf2 activity by helping recruit the E2 conjugating enzyme UbcH7 [29]. Recently, it was shown that the heat shock protein 90 (Hsp90) is a modifier of Smurf2-mediated receptor ubiquitination, as inhibiting Hsp90 activity led to an increased receptor ubiquitination [30]. This effect is due to the ability of Hsp90 to bind and chaperone the receptors.…”
Section: Regulation Of Tgfβ Receptor Stabilitymentioning
confidence: 99%
“…The chaperone protein, Hsp90, binds to TbRII and TbRI and protects them from association with the ubiquitin ligase Smurf2, thus stabilizing active receptor complexes and promoting Smad signaling downstream of TGF-b (Wrighton et al 2008). The adaptor protein TLP (TRAP-1-like protein) associates with TbRII (and activin receptors) and with Smad4 (Felici et al 2003).…”
Section: Signaling Via Tgf-b Receptors Is Modulated By Interactions Wmentioning
confidence: 99%